Informal Spaces in Global Citizenship Education - Madeleine Le Bourdon (Policy and Practice: A Development Education Review, 2018)
Literature on global citizenship education (GCE) has helped to build a framework of best practice for its implementation and delivery. Creating safe spaces and open environments for teaching, learning and discussion have been widely supported by scholars. However, while research shows that the constraints of formal education make it increasingly difficult to deliver GCE, there remains little in-depth research into the spaces beyond the walls of formal education as a place for GCE. Using data from fieldwork conducted within an international non-governmental organisation (INGO) aimed at building ‘active global citizens’, as well as reflections from working in the field, this article will argue that both as scholars and practitioners we need to understand in more depth the impact these informal spaces and encounters have on fostering global citizenship.